A classification framework for software requirements prioritization approaches - Martinez Carod, Nadina; Cechich, Alejandra (Revista Colombiana de Computación, 2009)
The task of eliciting requirements has became extremely difficult because stakeholders have different perspectives on an expectation on a system. Besides, the time to obtain the final product is limited. To overcome this situation, a requirements ranking may help in planning releases by indicating which functions are critical and which ones can be added, and in what order, over successive releases. The prioritizing process must hold stakeholder satisfaction considering high-priority requirements first. However, practical experience shows that prioritizing requirements is not as straightforward task as the literature suggests. Considering that, this paper has two goals: the first one is to present a classification framework for software requirements prioritization approaches (emphasizing differences and similarities among eleven selected approaches); and the second one is to show the approaches' weaknesses and to propose possible improvements for future research on this line.